Analysis of Three Phases Asynchronous Slip Ring Motor Performance Feedback Type 243 - Sardono Sarwito; Semin Semin; Achmad Suherman (Institut Teknologi Sepuluh Nopember, 2017)
Induction motor is an Alternating Current Electric Motor (AC), this motor most widely used. There are two types of rotor on three-phasess asynchronous motor, the squirrel-cage rotor and the slip ring rotor. Every motor has its own characteristic, it have been affect the used of the motor. In this research is aiming to know three-phasess asynchronous slip ring motor performance on unloaded and loaded condition. On its condition, the variation resistance starting from 0Ω - 25Ω. The results of three-phasess asynchronous slip ring motor on unloaded condition having maximum output power 58 W and maximum torque 0.22 Nm in 25Ω of resistance. While in the condition loaded having a maximum Pin 131,5 W, maximum Pout 109,31 W, maximum torque 2,08 Nm and maximum efficiency 95%. The analysis was done by knowing the relation between torque vs speed and efficiency vs load. The result shows that the increasing of motor speed have been give affect the decreasing of motor torque in according with the torque formula. In the other result, it can be seen that increasing of the load, efficiency have been increase